Microscopic effects of Dy doping in the topological insulator Bi2Te3 - Duffy, LB; Steinke, N-J; Krieger, JA; Figueroa, AI; Kummer, K; Lancaster, T; Giblin, SR; Pratt, FL; Blundell, SJ; Prokscha, T; Suter, A; Langridge, S; et al. (American Physical Society, 2018)
Magnetic doping with transition metal ions is the most widely used approach to break time-reversal symmetry in a topological insulator (TI)—a prerequisite for unlocking the TI’s exotic potential. Recently, we reported the doping of Bi2Te3 thin films with rare-earth ions, which, owing to their large magnetic moments, promise commensurately large magnetic gap openings in the topological surface states. However, only when doping with Dy has a sizable gap been observed in angle-resolved photoemission spectroscopy, which persists up to room temperature. Although disorder alone could be ruled out as a cause of the topological phase transition, a fundamental understanding of the magnetic and electronic properties of Dy-doped Bi2Te3 remained elusive. Here, we present an x-ray magnetic circular dichroism, polarized neutron reflectometry, muon-spin rotation, and resonant photoemission study of the microscopic magnetic and electronic properties. We find that the films are not simply paramagnetic but that instead the observed behavior can be well explained by the assumption of slowly fluctuating, inhomogeneous, magnetic patches with increasing volume fraction as the temperature decreases. At liquid helium temperatures, a large effective magnetization can be easily introduced by the application of moderate magnetic fields, implying that this material is very suitable for proximity coupling to an underlying ferromagnetic insulator or in a heterostructure with transition-metal-doped layers. However, the introduction of some charge carriers by the Dy dopants cannot be excluded at least in these highly doped samples. Nevertheless, we find that the magnetic order is not mediated via the conduction channel in these samples and therefore magnetic order and carrier concentration are expected to be independently controllable. This is not generally the case for transition-metal-doped topological insulators, and Dy doping should thus allow for improved TI quantum devices.